On the speedup required for work-conserving crossbar switches. - Krishna, P. (IEEE Journal on selected areas in communications)
This paper describes the architecture for a work-conserving server using a combined I/O-buffered crossbar switch. The switch employs a novel algorithm based on output occupancy, the lowest occupancy output first algorithm (LOOFA), and a speedup of only two. A work-conserving switch provides the same throughput performance as an output-buffered switch. The work-conserving property of the switch is independent of the switch size and input traffic pattern. We also present a suite of algorithms that can be used in combination with LOOFA. These algorithms determine the fairness and delay properties of the switch. We also describe a mechanism to provide delay bounds for real-time traffic using LOOFA. These delay bounds are achievable without requiring output-buffered switch emulation